An Analysis of Javino Middleware for Robotic Platforms Using Jason and JADE Frameworks - Junger, Dayana; Silva, João Victor Guinelli da; Pantoja, Carlos Eduardo (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2016)
Robotics is the field of knowledge in which it is possible to use agent-oriented programming languages to develop robots capable of interacting with their environment by using sensors and actuators. Some situations require that agents try to achieve tasks in the physical world by both sending commands to actuators and perceiving data from sensors. Based on this, Javino middleware can be employed to interconnect Java-based MAS and hardware devices. Thus, our main objective in this paper is to prove the usefulness of using Javino to perform the communication between MAS applications and Arduino boards. For this, we conduct experiments to analyze the Javino's performance in Jason and JADE frameworks and discover if there is any condition in which this middleware should not be used.